Enhancing Robotics with Cognitive Capabilities - Fatoye, Joseph (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
In the pursuit of creating more effective and adaptable robots, the flourishing field of cognitive robotics has arisen to infuse machines with human-like cognitive functions. This paper delves into the significance of cognitive robotics and charts a course for empowering robots with advanced cognitive capabilities. Drawing inspiration from current research in cognitive architectures, the paper underscores the importance of refined perception, language processing, complex decision-making, emotional intelligence, and cognitive synergy. By integrating these cognitive functions into robotic systems, the goal is to equip robots to operate intelligently in dynamic environments, collaborate seamlessly with humans, and adeptly handle diverse tasks. The proposed enhancements mark crucial strides towards the development of more versatile and capable intelligent robots.